THE ROLE AND IMPORTANCE OF PRACTISING PHYSICAL EXERCISES WITH THE PURPOSE OF PREVENTING A SEDENTARY, STRESSFUL AND DISCORDERED LIFE - Ioan Drăgoiu (Editura Univeristatii "Stefan cel Mare" din Suceava, 2019)
Physical education represents one of the oldest ways of the formative activity and it is a part of personality structuring. This part of the activity comprises a set of activities which contribute to the forming and developing of the human being, by valorising the psycho-physical dimensions of personality and by establishing a balance between physic and psychic, psycho-motion and the intellectual potential, emotionalism, affectivity and will. Starting from this idea, we think it is necessary to reconsider the place of physical education classes at school. Despite the general aims of the physical education curriculum, we notice a decrease of the interest for physical exercise. Charmed by the computer, some students ignore the physical education class, and they are even encouraged by their parents to do it. But school can be an important factor which has to contribute to forming physical exercise abilities, in an organised environment and individually, too, if the right decision are taken by people who are able to do it. Some steps have been done in this direction. Physical education has represented, lately, the topic of many meetings of several decision factors belonging to different fields, and the importance of this activity in getting and maintaining a high standard of life quality has always been admitted. If the programmes which have been initiated continue and if the number of physical education classes becomes bigger, there is hope that physical education will get the place it deserves in the life of the young generation.